The effect of gamma rays irradiation on diversity of Musa paradisiaca var. sapientum as revealed by ISSR molecular marker - MARIA SERVIANA DUE; ARI SUSILOWATI; AHMAD YUNUS (Society for Indonesian Biodiversity, 2019)
Abstract. Due MS, Susilowati A, Yunus A. 2019. The effect of gamma rays irradiation on diversity of Musa paradisiaca var. sapientum as revealed by ISSR molecular marker. Biodiversitas 20: 1416-1422. Pisang Ambon (Musa paradisiaca var. sapientum (L.) Kunt.) is one of the horticultural commodities that have high production in Indonesia, making it a superior product. Bananas are propagated vegetatively, which hampers the production of genetic variation and requires a long generation time in the vegetative cycle. This study aimed to determine the diversity of Pisang Ambon induced by gamma radiation of various dosages (10 Gy, 20 Gy and 30 Gy) in vitro based on the ISSR (Inter-Simple Sequence Repeats) marker. The results showed that gamma-ray radiation influenced the morphological properties of plant height, stem diameter, leaf length, leaf width and leaf number based on ANOVA variance analysis. Increased growth occurs in plants with radiation doses of 10 Gy and 20 Gy. The molecular analysis of ISSR uses 6 primers, namely ISSR 835, ISSR 836, ISSR 846, ISSR 847, ISSR 848 and ISSR 855. Of the 6 primers, only 2 primers were able to produce polymorphisms above 50%. A total of 9 bands were produced, in which 8 bands showed polymorphic with a percentage of 90%. The similarity matrix ranged from 0.25-0.93, indicating the level of variation between mutants. The result of dendrogram was divided into two groups with a coefficient distance of 0.47-0.93; plants at a dose of 10 Gy have the highest diversity with the furthest coefficient of diversity distance of 0.47.